2013
DOI: 10.1002/app.39825
|View full text |Cite
|
Sign up to set email alerts
|

Frontal polymerization of superabsorbent nanocomposites based on montmorillonite and polyacrylic acid with enhanced soil properties

Abstract: Polyacrylic acid/montmorillonite(MMT)/carboxymethylcellulose (CMC) superabsorbent nanocomposites were prepared by frontal polymerization (FP), an economic method characterized by low-energy consumption and short-reaction time. They were characterized by Fourier transform infrared spectroscopy, X-ray diffraction, transmission electron microscopy, and scanning electron microscopy. The effects of reaction parameters on the front propagation and the water absorbency of the nanocomposites were investigated. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
(46 reference statements)
1
13
0
Order By: Relevance
“…As a fast and efficient polymerization model, frontal polymerization (FP) has received special attention because it can rapidly produce a variety of functional polymers and polymeric networks toward unique applications, including soft contact lenses, sensors, controlled drug delivery materials, tissue engineering, wound dressing, diagnostics, and soft robots . Particularly, FP has been broadly employed to produce various hydrogels such as starch‐graft‐poly(acrylic acid) hydrogels, porous polyacrylamide hydrogels, poly( N,N ‐dimethylacrylamide) hydrogels, superabsorbent hydrogels, graphene‐containing stimuli‐responsive polymer hydrogels, functional hybrid composite hydrogels, amphiphilic hydrogels, N ‐vinylimidazole‐based hydrogels, and interpenetrating polymer networks hydrogels . However, there are few reports on the investigation of hydrogels derived from FP for the removal of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…As a fast and efficient polymerization model, frontal polymerization (FP) has received special attention because it can rapidly produce a variety of functional polymers and polymeric networks toward unique applications, including soft contact lenses, sensors, controlled drug delivery materials, tissue engineering, wound dressing, diagnostics, and soft robots . Particularly, FP has been broadly employed to produce various hydrogels such as starch‐graft‐poly(acrylic acid) hydrogels, porous polyacrylamide hydrogels, poly( N,N ‐dimethylacrylamide) hydrogels, superabsorbent hydrogels, graphene‐containing stimuli‐responsive polymer hydrogels, functional hybrid composite hydrogels, amphiphilic hydrogels, N ‐vinylimidazole‐based hydrogels, and interpenetrating polymer networks hydrogels . However, there are few reports on the investigation of hydrogels derived from FP for the removal of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Superabsorbent hydrogel (SAP) usually are used as soil conditioners and chemical formulations in agriculture to maintain soil moisture and enhance the pesticide efficiency 17 . However, some research showed when pesticides coexisted with SAP, the environmental fate and transformation of pesticides could be changed, especially for bound residue 12,13,18 .…”
Section: Discussionmentioning
confidence: 99%
“…Our group has prepared polyacrylic acid (PAA)/MMT/sodium carboxymethyl cellulose (CMC) superabsorbent nanocomposite via FP. Compared with BP, the product showed better salt resistance, thermal stability, and large size and number of soil water stable macro‐aggregates . But when MMT content exceeds 5 wt%, the propagating front could not be sustained and it is not conducive to lower production costs if MMT content is low.…”
Section: Introductionmentioning
confidence: 98%